(untitled) (INNOVATIVE ECONOMY, 2026)
Kryvokulska N.M., Hunko S.I. STRATEGIC SCENARIOS FOR THE CLUSTER ORGANIZATION OF THE REGIONAL MUNICIPAL SOLID WASTE MANAGEMENT SYSTEM (A CASE STUDY OF TERNOPIL REGION) Purpose. The aim of the article is to develop strategic scenarios for the cluster organization of the regional municipal solid waste management system, taking into account the spatial and logistical, institutional, and social and service parameters of the territory (a case study of Ternopil Oblast) and to substantiate the selection of the optimal scenario. Methodology of research. The methodological basis of the study is the combination of systemic, scenario-based, and target-oriented approaches to the organization of the regional municipal solid waste management system. The article applies the methods of structural and functional analysis – to substantiate the hierarchy of waste management priorities and determine the instruments and performance indicators for their implementation; comparative analysis – to compare alternative strategic scenarios of cluster organization; spatial and logistical analysis – to assess the territorial configuration of clusters and minimize transportation distances; analytical generalization – to formulate conclusions regarding the selection of the optimal scenario for the cluster organization of the regional municipal solid waste management system of Ternopil Oblast. The information base of the study includes regulatory legal acts of Ukraine, Methodological Recommendations for the Development of Regional Waste Management Plans, and statistical and analytical materials of the Department of Ecology and Natural Resources of the Ternopil Regional Military Administration. Findings. From the perspective of the target-oriented approach, the expediency of forming a cluster model of the regional municipal solid waste management system as an instrument for achieving the indicators of the five-stage waste management hierarchy has been substantiated. Three alternative strategic scenarios for clustering the territory of Ternopil Oblast have been developed and analysed, differing in spatial and logistical configuration, institutional logic of formation, and the level of territorial balance. The comparative assessment made it possible to identify spatial and logistical disproportions in the examined options based exclusively on the administrative division, to determine the risks of infrastructural overload and concentration of waste flows, and to substantiate the selection of the most balanced scenario of dividing the oblast into four clusters based on optimal logistics. It has been proven that the proposed scenario of cluster organization of the regional municipal solid waste management system creates prerequisites for enhancing institutional manageability, reducing transportation costs, and gradually transitioning to the principles of the circular economy. Originality. The approach to the strategic substantiation of the territorial organization of the regional municipal solid waste management system based on the combination of target-oriented and scenario-based approaches has been improved. Unlike existing approaches, which mainly focus on the administrative and territorial principle of division or individual logistical parameters of system functioning, the proposed approach integrates the target guidelines of the waste management hierarchy with alternative spatial configurations of clusters, ensuring a comprehensive assessment of their long-term environmental, social and economic consequences. Practical value. The proposed strategic scenario of dividing Ternopil Oblast into four clusters based on optimal logistics can be used in the development of the Regional Waste Management Plan, the formation of investment programs, the preparation of inter-municipal cooperation projects, and the implementation of measures aimed at achieving the target indicators of the waste management hierarchy. Key words: sustainable development; circular economy; regional waste management system; municipal solid waste; strategic scenarios; territorial clustering; spatial and logistical optimization; regional planning.